2018
DOI: 10.1111/bjd.16740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, dermoscopic, histological and molecular analysis of BAP1-inactivated melanocytic naevus/tumour in two familial cases of BAP1 syndrome

Abstract: DEAR EDITOR, BRCA1-associated protein (BAP)1-inactivated melanocytic naevus/tumours (BIMN/Ts) are specific skin tumours that appear during the first two decades of life. 1 These lesions must be recognized by dermatologists and pathologists as an early predictive marker of BAP1 cancer syndrome, as they may precede the development of uveal and cutaneous melanomas, mesotheliomas, lung adenocarcinomas, renal cell carcinomas and meningiomas by several years. 2,3 The dermoscopic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…Dermoscopic features of BIMTs have been anecdotally reported and include the presence of pink structureless areas with peripheral linear vessels, 6, 7, 9 a multicomponent pattern, 9 and pink structureless areas with peripheral pigmented globules. 8 In the present study we have identified 3 additional dermoscopic patterns: structureless pink-to-tan, network with raised structureless pink-to-tan areas, and globular patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermoscopic features of BIMTs have been anecdotally reported and include the presence of pink structureless areas with peripheral linear vessels, 6, 7, 9 a multicomponent pattern, 9 and pink structureless areas with peripheral pigmented globules. 8 In the present study we have identified 3 additional dermoscopic patterns: structureless pink-to-tan, network with raised structureless pink-to-tan areas, and globular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 There are limited reports on the clinical characteristics of BIMT 3,5 and data regarding the dermoscopic appearances of these lesions are sparse. [6][7][8][9] Herein we sought to describe and correlate the clinical and dermoscopic findings associated with BIMT, features that may raise suspicion for germline BAP1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, BIMTs have yet to be characterized by confocal microscopy, and only a few studies have described their dermoscopic aspects [8, 10, 11]. Here, we report our comprehensive characterization of the clinical and genetic traits of a BAP1 mutation carrier.…”
Section: Introductionmentioning
confidence: 99%
“…BAP1-inactivated melanocytic tumors (BIMTs), also known as "bapomas" or "BAP1-deficient tumors," are melanocytic nevi that clinically appear as dome-shaped, pink papules, resembling dermal nevi or fibromas (Fig. 9a-b) (Haugh et al 2017;Moawad et al 2018). These nevi display a distinct histopathological profile, with a predominantly dermal proliferation of melanocytes that includes a combination of larger epithelioid ("spitzoid") melanocytes, as well as "conventional" smaller melanocytes (Wiesner et al 2011).…”
Section: Bap1-inactivated Melanocytic Tumorsmentioning
confidence: 99%